Tanggung Jawab Hukum Direksi atas Keamanan Siber dalam Tata Kelola Perusahaan Digital - burhanudin (RETORIKA: Journal of Law, Social, and Humanities, 2026)
This study aims to analyze the regulation of the board of directors' liability regarding cybersecurity within digital corporate governance under Indonesian law and to formulate a legal framework that provides legal certainty regarding such liability. The study employs a normative legal research method, utilizing both statutory and conceptual approaches. Legal materials comprising primary, secondary, and tertiary sources were gathered through literature review and analyzed using relevant legal interpretation, legal theory, and legal principles. The findings indicate that the board of directors' liability for cybersecurity constitutes part of the company's management function, as it relates to digital risk management, the reliability of electronic systems, and data protection. The legal framework for directors' liability must position cybersecurity as an integral part of corporate strategic policy by strengthening governance, oversight, and risk control. Strengthening the standards of directors' obligations is essential to strike a balance between protecting the company's interests and ensuring legal certainty in digital business operations, while also safeguarding stakeholders within the rapidly evolving information technology-based business ecosystem.